Analysis of Investors’ Reaction to Unexpected Earnings Under Market Uncertainty - narges hamidian; Mehdi Arabsalehi; hadi amiri (Journal of Asset Management and Financing, 2020)
Objectives: Under uncertainty, investors do not have enough information about the firm's future cash flows and there is ambiguity about future state of the market. In this situation, according to Bayes' rule, when the market receives information signals (such as firms’ earnings announcements), it may reduce uncertainty and results in more investors' reaction to earnings announcement. The purpose of this study is investigating investors' reaction to unexpected earnings under market uncertainty. Method: For doing so, a sample of 162 companies listed in the Tehran Stock Exchange in the period 1384 to 1394 have been selected. Two methods (the computational formula and GARCH method) were used for calculating market uncertainty. Results: The results of hypotheses test indicated when market uncertainty is high (compared to lower uncertainty), investors’ reaction to earnings announcement is more. Also, under high market uncertainty, investors display more reaction to bad news that this response is consistent with the conservatism approach.